The Effectiveness of Medical and Vocational Interventions for Reducing Sick Leave of Self-Employed Workers - Stijn Baert; Bas van der Klaauw; A. Gijsbert C. van Lomwel (Institute for the Study of Labor (IZA), 2016)
We investigate whether interventions by (i) medical doctors and (ii) occupational specialists are effective in reducing sick leave durations among self-employed workers. To this end, we exploit unique administrative data comprising all sick leave claims by self-employed workers insured with the major Dutch private insurer between January 2009 and March 2014. We estimate a multivariate duration model dealing with non-random selection into the two intervention types by controlling for observable and unobservable claimant characteristics. We find adverse treatment effects for both interventions, which are heterogeneous by the physical toughness of the claimants' occupation.
Keywords: C41; I13; J22; R31; 330; sickness absenteeism; self-employment; medical interventions; dynamic treatment effects